Historisitas Tahfidzul Qur’an: Upaya Melacak Tradisi Tahfidz di Nusantara - Noer, Syaifudin (JOIES (Journal of Islamic Education Studies), 2021)
The tradition of tahfidz (memorizing the Koran) is exist since the time of the Prophet Muhammad. which the Prophet had exemplified with his companions. In Indonesia itself, the journey of the tahfidz tradition goes through three main periods, namely pre-independence, post-independence to the Reformation era (MTQ 1981). In pre-independence, there were 5 sanad that had a role in the spread of tahfidz al-Qur'an and were a source of hufadz in tahfidz institutions/pesantren, including KH. Muhammad Said bin Ismail Sampang, Madura, KH. Munawaar from Sidayu, Gresik, Muhammad Mahfudz at-Tarmasi. Termas Pacitan, KH. Muhammad Munawwir Krapyak, Yogyakarta and KH. M. Dahlan Khalil from Rejoso, Jombang. After independence, a new Tahfidz institution emerged, which was pioneered by KH. Muntaha (1912-2004 AD) Pesantren Al 'Asy'ariyah Wonosobo-Central Java and KH. Yusuf Junaidi (1921-1987) Bogor. Over time, the Tahfidz Institute was formed after the Musabaqah Hifdzil Quran (MHQ) developed on the islands of Java and Sulawesi, so since 1981 until now almost all regions in the archipelago.